An ANP Model to Generate Performance Indicators for Manufacturing Firms Under a Balanced Scorecard Approach. Issue 1 (2nd January 2022) - Quezada, Luis E.; Aguilera, Daniel E.; Palominos, Pedro I.; Oddershede, Astrid M.
Abstract: This paper presents a method that supports a process for the generation of performance indicators for manufacturing areas within companies. The existing literature in the area of performance management presents frameworks to guide the selection of performance indicators. Particularly, the literature shows the use of multicriteria decision making methods (MCDM) for selecting indicators from a set of predefined ones. This paper goes beyond by developing a method to support the generation of the performance indicators for the manufacturing area. This process is supported by the Analytic Network Process (ANP). The network model, which is based on a Balanced Scorecard (BSC) framework, includes nodes that are grouped into five clusters: long-term objectives, strategic business units, critical success factors, manufacturing decision areas, and human resource management. The proposed method consists of the following major steps: assigning weights to the manufacturing decision areas, diagnosing these areas, and generating performance indices ranked from high to low. The proposed method allows managers to define performance indicators for the manufacturing area that are aligned with the company's long-term strategic objectives. This is done by the use of an ANP model that captures the complex relationships that exist between the various strategic objectives of the strategy map of a company. As an illustration, an application in a company that produces pork-based food is described. The managers found that the proposed method was easy to understand and easy to follow, and that it was useful for defining performance measures.